Systematic review and meta-analyses of the long-term efficacy of narrative exposure therapy for adults, children and perpetrators - Siehl, Sebastian; Robjant, Katy; Crombach, Anselm (Psychotherapy research, 2021)
Objective: Narrative Exposure Therapy (NET) is a short-term trauma-focused intervention originally developed for treating survivors of war and torture. The neurobiological theoretical foundations of NET would suggest that the approach should have long term beneficial effects. We tested this assumption and also provided an extensive overview of all NET studies for adults, for children (KIDNET), and for perpetrators (Forensic Offender Rehabilitation NET; FORNET). Method: Following a systematic literature review, we conducted meta-analyses with all studies that had control conditions, and with all Randomized Controlled Trials (RCTs). We assessed between-groups short- (< 6 months) and long-term (≥ 6 months) effect sizes for symptoms of posttraumatic stress disorder (PTSD) and depression. Results: In a total of 56 studies from 30 countries comparing 1370 participants treated with NET to 1055 controls, we found large between group effect sizes regarding the reduction of PTSD symptoms in favor of NET. Analyses of RCTs with active controls yielded small to medium effect sizes in the short-term, and large effect sizes in the long-term. Conclusions: NET, KIDNET, and FORNET yield beneficial and sustainable treatment results for severely traumatized individuals living in adverse circumstances. Studies in highly developed health care systems comparing NET with other evidence-based trauma-focused interventions are needed.
Gesehen am 05.04.2024
Online veröffentlicht: 18. November 2020